Application site adverse events associated with the buprenorphine transdermal system: a pooled analysis. (May 2013) - Wen, Warren; Lynch, Shau Yu; Munera, Catherine; Swanton, Ruth; Ripa, Steven R; Maibach, Howard
<x xml:space="preserve">Abstract</x> Objective: To characterize the profile of application site reactions (ASRs) for patients treated with the buprenorphine transdermal system (BTDS) in chronic pain studies. Methods: The incidences of ASRs during treatment with BTDS were examined using (a) integrated data from 16 controlled and uncontrolled Phase III chronic pain studies (N = 6566), (b) a subset of integrated data that focused on the double-blind phases of five enriched, placebo-controlled studies (n = 1806) and (c) data from an international postmarketing drug safety database. These data were compared with the ASR data reported in the full prescribing information of other transdermal patches marketed in the US. Results: Among the 6566 patients, the overall incidence of ASRs was 23.4%, of which 98.3% were mild to moderate in intensity, none were serious and 4.4% led to treatment discontinuation. Rates of severe and inflammatory ASRs were low. Among the 1806 patients, ASR rates were higher with BTDS (16.6%) than placebo transdermal system (12.7%). Among the 6566 patients, the 1806 patients, and the postmarketing data, the most common ASRs seen were pruritus, erythema and rash. Incidences of most ASRs for other selected transdermal products were 17% or lower. Conclusion: Incidence rates of ASRs in patients treated with BTDS were low and infrequently led to discontinuation. Severe and inflammatory-type ASRs were not common. The ASR profile of BTDS was comparable with those of other transdermal patches.